IDDF2020-ABS-0209 Asian prevalent allele at ABCB5 SNP Rs10254317 associates with hepatocellular carcinoma (HCC) risk and adverse clinical outcomes. (18th November 2020) - Yeung, Philip Chun; Chong, Charing Ching-Ning; Cheung, Tan To; Chai Ng, Kelvin Kwok; Lai, Paul Bo San; Cheung, Siu Tim
Abstract : Background: Ethnic disparities in the prevalence of hepatocellular carcinoma (HCC) continue to exist. Highest age-adjusted HCC incidence rates are recorded in East Asia, and 55% of HCC cases worldwide are from China. Meanwhile, ABCB5 has been reported to be overexpressed in HCC and associated with poor survival. To evaluate the ethnic differences, allele frequencies of ABCB5 SNP rs10254317 in the local cohort were compared with those from Chinese and Caucasian in 1000 Genomes project, and their clinical implications on HCC patients were studied. Methods: A total of 300 HCC and 300 healthy blood samples (99.3% and 94.7% Chinese respectively) were prospectively collected with informed consent. All patients had been diagnosed with primary HCC and underwent partial hepatectomy. Clinicopathological information including sex, age, tumour stage and survival outcomes were collected prospectively. Genomic DNA was extracted from blood samples and SNPs were examined. For comparison, genomics data and corresponding clinical information for HCC were obtained from The Cancer Genome Atlas (TCGA). SNP allele frequencies in different populations were obtained from 1000 Genomes Browser by NCBI. Results: Allele frequencies of rs10254317 observed in healthy local cohorts (G: 0.334 vs A: 0.666) were comparable to Northern and Southern Chinese (CHB; G: 0.311 vs A: 0.689; CHS; G: 0.286 vs A: 0.714) in 1000 Genomes project, which were significantly different from Caucasian (GBR; G: 0.615 vs A: 0.385) (p<0.001). Chinese-dominant allele frequency (AA/AG) associated with higher HCC risk (OR: 2.059, 95%CI: 1.16–3.67, p=0.014), advanced tumor stage (OR: 4.514, 95%CI: 1.02–19.96, p=0.047) and presence of venous infiltration (OR: 2.864, 95%CI: 1.00–8.18, p=0.049) from local cohort. TCGA HCC dataset also revealed a disparity in HCC survival outcomes among different populations, as elevated ABCB5 expression levels associated with poor survival in Asian HCCs but not in Caucasian HCCs (figure 1 ). Conclusions: Dominant allele of rs10254317 in ABCB5 among Chinese associates with risk of HCC and adverse clinical outcomes in HCC patients, which may also contribute to the ethnic disparity in HCC incidence and survival outcomes. Further investigation on SNPs of HCC-related genes with ethnic disparities are warranted.